2019
DOI: 10.1002/ccr3.1952
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive skeletal muscle metastasis from cervical cancer invading into the spinal canal: A case report

Abstract: Key Clinical Message We present the first case of the patient with skeletal metastasis of uterine cervical cancer which invaded the vertebral body and spinal canal, with consequent paralysis of the lower extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In another study spanning over 30 years, Plaza et al identified 118 cases of soft tissue metastases, with only two cases (located in the gluteus and thigh), involving squamous cell carcinoma of the cervix [4]. Miyoshi Ai et al, described a case of cervical carcinoma metastasis to the latissimus dorsi muscle, surgically treated, with subsequent recurrence of metastasis in the D7 vertebral body invading the vertebral canal [5]. Some authors reporting these types of localizations also acknowledge the exceptional nature of such metastasis, hindering a clear management approach for these cases [3,5,6].…”
Section: /4mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study spanning over 30 years, Plaza et al identified 118 cases of soft tissue metastases, with only two cases (located in the gluteus and thigh), involving squamous cell carcinoma of the cervix [4]. Miyoshi Ai et al, described a case of cervical carcinoma metastasis to the latissimus dorsi muscle, surgically treated, with subsequent recurrence of metastasis in the D7 vertebral body invading the vertebral canal [5]. Some authors reporting these types of localizations also acknowledge the exceptional nature of such metastasis, hindering a clear management approach for these cases [3,5,6].…”
Section: /4mentioning
confidence: 99%
“…Miyoshi Ai et al, described a case of cervical carcinoma metastasis to the latissimus dorsi muscle, surgically treated, with subsequent recurrence of metastasis in the D7 vertebral body invading the vertebral canal [5]. Some authors reporting these types of localizations also acknowledge the exceptional nature of such metastasis, hindering a clear management approach for these cases [3,5,6].…”
Section: /4mentioning
confidence: 99%